2021
DOI: 10.3201/eid2703.204253
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Tuberculosis Burden in Vietnam Measured by Consecutive National Surveys, 2007–2017

Abstract: Vietnam, a high tuberculosis (TB) burden country, conducted national TB prevalence surveys in 2007 and 2017. In both surveys participants were screened by using a questionnaire and chest radiograph; sputum samples were then collected to test for Mycobacterium tuberculosis by smear microscopy and Löwenstein-Jensen culture. Culture-positive, smear-positive, and smear-negative TB cases were defined by laboratory results, and the prevalence of tuberculosis was compared between the 2 surveys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…However, economic growth and reduction in poverty may not be the only explanation for the change, as there were also improvements in tuberculosis diagnostics and health service access through an expansion of health insurance in Vie ˙t Nam [19,20]. Possible explanations for the results of our study therefore include that the rapid economic development in Vie ˙t Nam led to tuberculosis patients being wealthier in the second survey.…”
Section: Plos Medicinementioning
confidence: 80%
See 4 more Smart Citations
“…However, economic growth and reduction in poverty may not be the only explanation for the change, as there were also improvements in tuberculosis diagnostics and health service access through an expansion of health insurance in Vie ˙t Nam [19,20]. Possible explanations for the results of our study therefore include that the rapid economic development in Vie ˙t Nam led to tuberculosis patients being wealthier in the second survey.…”
Section: Plos Medicinementioning
confidence: 80%
“…The study found a 37% reduction in the prevalence of culture-positive tuberculosis, a 53% reduction in the prevalence of smear-positive tuberculosis, and no significant reduction in smear-negative or subclinical tuberculosis. The change in tuberculosis prevalence was more pronounced among men, among people living in rural areas, and in provinces in the north and south of the country [20].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations